MANAJEMEN STRES DI LEMBAGA PENDIDIKAN ISLAM: Studi Mahasiswa Dalam Menghadapi Tugas Akhir Submit Jurnal - Muh. Ibnu Sholeh; Sulistyorini (re-JIEM (Research Journal of Islamic Education Management), 2022)
Job demands will cause stress if they cannot be completed on time, especially if the task has not been mastered because, with existing limitations, assignments given by lecturers often affect students psychologically. The method used to conduct this research uses library research while collecting data through related references, both offline and online. The data obtained is then processed to be more complete and up to date. Data analysis uses analysis through various related literature. The results of the analysis show that there is a need for stress management so that it does not tend to be negative, and can be positive for these students, while the causes of stress consist of (1) environmental factors; (2) institutional factors; and (3) personal factors. These factors can be specified according to each condition. The suggestions for these problems include (1) making clear plans, (2) avoiding delays in work and assignments, grouping tasks into several parts, (3) seeking support from people around them, (4) getting enough rest, (5) exercising and good nutrition, (6) use relaxation techniques, and (7) seek professional help when necessary.